2023
DOI: 10.25122/jml-2022-0091
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease: relation to juvenile obesity, lipid profile, and hepatic enzymes

Abstract: The prevalence of juvenile obesity is increasing, reaching epidemic proportions, presenting a link not only to NAFLD (non-alcoholic fatty liver disease) but to abnormal lipid profiles and liver enzyme abnormalities. Liver ultrasonography is a sensitive and specific tool for the recognition of NAFLD. This study aims to assess the association between NAFLD and juvenile obesity and to determine the other related changes in a set of indicators, including lipid profile abnormalities and serum transaminases. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, further research is needed to determine the most appropriate strategies for implementing pharmacogenetic testing in clinical practice and to evaluate the clinical and economic benefits of these strategies. [ 53 , 54 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further research is needed to determine the most appropriate strategies for implementing pharmacogenetic testing in clinical practice and to evaluate the clinical and economic benefits of these strategies. [ 53 , 54 ]…”
Section: Discussionmentioning
confidence: 99%
“…in their study recruiting 400 Iraqi healthy individuals of Arab, Kurd, and Turkmen ethnicity found these alleles heterozygotes of CYP2C9 * 2 in 0.19%, CYP2C9 * 3 in 0.14%, and CYP2C9 * 5 in 0.01%. [ 23 , 24 ] Abd Alridha AM et al . [ 25 ] found only two alleles CYP2C9 * 2 in 13.7% and CYP2C9 * 3 in 9.4% in their study including 80 patients of cardiovascular diseases.…”
Section: R Esultsmentioning
confidence: 99%
“…Limiting protein intake can reduce indoxyl sulfate production, and a low-protein diet supplemented with keto analogues has been shown to decrease serum indoxyl sulfate levels. Administration of activated charcoal has also been reported to lower indoxyl sulfate plasma levels in CKD patients [33][34][35][36].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…tiliaceus was employed as a febrifuge, laxative, resolvent, and emollient in Indian medicine. Its fruit juice has been applied to the skin to treat weakness [13][14][15]. This research investigated the possible anti-obesity effects of two-graded doses of Iraqi Hibiscus tiliaceus leaves extract, alone and in combination with orlistat, on high-fat diet-induced obesity in male rats [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%